Bridging Mechanisms, Social Learning and Participation Dynamics in Community-Based Development - Obadia Mugabirwe; Noel Kansiime; Anthony Mpeirwe (Pondok Pesantren As-salafiyah Asy-syafi'iyyah, 2026)
Community-based development (CBD) initiatives are increasingly promoted as participatory approaches to sustainable local development; however, their effectiveness remains constrained by fragmented coordination, weak stakeholder collaboration, and limited knowledge exchange across institutional and community boundaries. While bridging mechanisms have been widely recognized as important instruments for connecting diverse actors, limited research has examined how these mechanisms differentially influence technical and social learning processes and the governance consequences of such differences. This study explores the role of bridging mechanisms in facilitating learning and collaborative governance within CBD initiatives in two rural districts of Western Uganda. Using an exploratory qualitative design, data were collected through 30 semi-structured interviews, three focus group discussions, and documentary analysis. The findings indicate that local non-governmental organizations and community-based organizations (26.1%), participatory platforms (21.7%), and boundary spanners (20.3%) constitute the primary bridging mechanisms supporting community development activities. However, their effectiveness is undermined by structural constraints, particularly elite capture (34% of reported challenges) and dependence on external funding sources. A significant finding is the distinction between technical learning, which accounted for 62% of observed learning outcomes, and social learning, representing 38%. The results reveal that bridging mechanisms predominantly facilitate technical knowledge transfer while providing insufficient support for trust-building, relational coordination, and collective meaning-making. Furthermore, weaker social learning environments were associated with higher levels of elite capture, suggesting a reinforcing relationship between low trust and exclusionary governance practices. The study proposes a relational–institutional model in which community trust and governance integration function as complementary enabling conditions for effective CBD implementation. These findings highlight the need to strengthen both bridging structures and social learning processes to enhance collaboration, governance quality, and long-term development effectiveness.